SAT0591 Local steroid injection versus wrist splinting for carpal tunnel syndrome: a randomized clinical trial. (15th June 2017) - So, H; Chung, V; Cheng, J; Yip, ML
Abstract : Background: Carpal tunnel syndrome (CTS) can lead to significant symptoms and loss of hand function. It also has a great socio-economic impact. However, there is no consensus regarding its best treatment up to this moment. Local steroid injection and wrist splinting are among the most popular nonsurgical treatment options. Previous studies have confirmed their respective effectiveness. However, there is no high quality head to head comparative study regarding the two treatments in the literature. Objectives: To compare the efficacy of local steroid injection and nocturnal wrist spiniting for CTS. Methods: We conducted a prospective randomised parallel clinical trial comparing the efficacy of local steroid injection and nocturnal wrist splinting in patients with CTS. The well validated and disease specific Boston Carpal Tunnel Questionnaire (BCTQ) was employed and its score at 4 weeks after treatment was used as the primary outcome measure. Important secondary outcomes included the patient satisfaction, the change of an objective finger dexterity test 9-hole-peg test, and the side effects. Results: Twenty-five patients in the local steroid group and 25 patients in the wrist splinting group completed the study procedures. The baseline patient and clinical characteristics of the two treatment groups were similar. At 4 weeks after treatment, there was significant improvement of the BTCQ scores in both the steroid group and splinting group. There was improvement of the 9-hole-peg test only in the steroid group but not in the splinting group. However, there was no statistically significant difference in the changes of BTCQ scores between the two groups after treatment. Patient satisfaction score was higher in the steroid group. Patient in the steroid group took less painkillers after treatment. Four patients developed side effects after splinting and 3 after local steroid injection, which was not statistically significant. Conclusions: Although local steroid injection and nocturnal wrist splinting were equally effective in the treatment of patients with CTS, only the former improved objective hand function. Local steroid injection also resulted in better patient satisfaction and less painkiller use without causing more side effects. Disclosure of Interest: None declared